Construction site safety control with medium-accuracy location data - Edrei, Tsah; Isaac, Shabtai (Journal of Civil Engineering and Management, 2017)
A statistical safety control method is presented that utilizes location data from a relatively inaccurate yet cost-effective system to track workers in real time, and prevent unsafe situations at construction sites. In light of the inaccuracy of the tracking system, buffer areas are defined as statistical zones, at some distance from potential workplace hazards. Statistical alerts are created according to predefined rules when the hazard exposure of workers in those zones crosses a certain threshold. The results of tests of the method demonstrate that the model is able to successfully process the location data in order to compensate for its inaccuracy. This is done without necessitating a significant increase in the areas that are defined as being of high risk, and therefore off-limits for most workers on site. The model can thus ensure the efficiency of the construction work by restricting the size of the areas on site that are off-limits for most workers, while at the same time ensuring the safety of workers. The method can also ensure that alerts will not be ignored by using statistical rules to avoid an excessive number of alerts, and by discerning who should be the client of an alert. First published online: 22 Jun 2016